Developing a small footprint and low-cost solar charge controller - Azhar A.D.; Hamid F.A.; Ghazali A.; Zuhdi A.W.M. (Institute of Electrical and Electronics Engineers Inc., 2025)
The need for renewable energy has been increasing rapidly nowadays in parallel to the depletion of fossil fuels to meet the global energy demand. Solar PV plays a key role in responding to this necessity. A solar PV system contains a solar panel as the source, a battery as the load, and a DC/DC converter to convert voltage from the solar panel to the battery. An additional significant component, which is a solar charge controller that integrates an algorithm into the converter, must be included to ensure the system works efficiently. On another hand, the controller is responsible for protecting the battery from unnecessary problems. In this paper, a solar charge controller was developed by using a synchronous buck converter topology. P&O MPPT algorithm was implemented in the controller to track the maximum power from the solar panel to gain high efficiency. A schematic diagram was designed by using low-cost components and Arduino Uno as the microcontroller. Then, a board layout was developed with a small footprint with a size of 63.5mm x 57mm. A lab measurement was done to test the functionality of the controller showed that it converted the voltage as supposedly. Lastly, a field measurement was done under two conditions: high and irregular irradiation. The solar charge controller was able to operate with the highest efficiency of 90.32% during high irradiation with the MPPT algorithm tracked successfully. ?2024 IEEE.